Eventratio diaphragmatica - Subagjo Martodipuro; Nurjono Sunarjo; Pitono Suparto; L. Partana (Indonesian Pediatric Society, 1973)
A diaphragmatic eventration is a displacement of abdominal structures into the thoracic cavity, due to weakness and balooning of the diaphragm (Nelson, 1969). In several aspects it has similarities with aÂ diaphragmatic hernia, i.e. the space occupying effects to the lungs, and the sequences of it. An eventration can be divided in 2 groups, the congenital eventration, where the diaphragm is devoid of mucles and only a membrane is separating the abdominal from the pleural cavity; and the acquired one where the phrenic nerve is damaged, usually due to birth injury; but it can also be caused by any other trauma (Bernado et aI., 1961; Bisono et aI., 1970) such as surgical procedures at the time of thoracotomy, the so called iatrogenic Â eventration (Jewett et aI., 1964).